Preparation method and application of high-compaction-density composite sodium ferric phosphate

Through ion chelation preparation technology and calcination process, the problems of low compaction density and insufficient electrochemical performance of composite sodium iron phosphate materials in sodium ion battery applications are solved, and high compaction density, low porosity and low cost are achieved. Material preparation improves the overall performance and safety of the material.

CN119330324AActive Publication Date: 2025-01-21深圳华钠新材有限责任公司

Patent Information

Application Number
CN202411460741.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing composite sodium ferric phosphate (NFPP) materials face problems such as low compaction density, high porosity, high processing cost, low synthesis efficiency, insufficient electrochemical performance, and limited industrial application in sodium ion battery applications.

Method used

Using ion chelation preparation technology, the sodium source, iron source, and phosphorus source are mixed according to a specific stoichiometric ratio, and reacted at a certain temperature, followed by sand grinding and spray drying, and then calcined in a tube furnace to control the interaction between pyrophosphate and The proportion of phosphate radicals reduces gas release and improves the density and stability of the material.

Benefits of technology

Significantly improve the compaction density and dynamic properties of the material, reduce the synthesis cost, improve the thermal stability and chemical stability of the material, optimize the electrochemical performance and safety, and promote the widespread use of NFPP materials in the field of sodium-ion batteries application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330324A_ABST
    Figure CN119330324A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of high-compaction-density composite sodium ferric phosphate. The preparation method comprises the following steps: weighing a sodium source, an iron source and a phosphorus source according to a stoichiometric ratio of [xNa + (a-x) A]: [yFe + (b-y) B]: P = a: b: (c + 2), mixing and dispersing the iron source, the sodium source, the phosphorus source and a chelating agent into pure water, reacting for a period of time at a certain temperature, transferring into a sand mill for grinding, adding a dispersing agent, cane sugar, the dopants A and B, and obtaining slurry F after grinding; and carrying out spray drying on the slurry F to obtain powder K. The powder K is transferred to a tubular furnace, and the oxygen content is 1t under the N2 protective atmosphere; and calcining at the temperature of 450-600 DEG C under the pressure of 50 ppm, and then carrying out air jet pulverization to obtain sodium ferric pyrophosphate positive electrode material powder with high compaction density and a molecular formula of (NaxAa-x) (FeyBb-y) (PO4) cP2O7. When the product is used, the compaction density is high, the dynamic performance of the material is enhanced, the thermal stability and chemical stability of the material are improved, and the electrochemical performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a high compaction density composite sodium iron phosphate, a preparation method thereof, and applications thereof. Background Art

[0002] With the advancement of global energy transformation and sustainable development, new energy storage technology is developing rapidly. Among them, sodium-ion batteries are regarded as an important choice for large-scale energy storage systems due to their advantages such as abundant resources, low cost and environmental friendliness. As the decisive factor in the performance of sodium-ion batteries, the performance of positive electrode materials directly affects the energy density, cycle stability and safety of batteries. Composite sodium iron phosphate (NFPP) materials are favored by researchers due to their good cycle stability, ultra-high safety performance and excellent rate performance.

[0003] However, the existing composite sodium iron phosphate (NFPP) materials still face many challenges in practical applications. The technical problems mainly include:

[0004] 1. Low compaction density: The density of the material in its natural state is insufficient (generally compaction density 2.0, true density 3.2), which limits its energy density in battery applications.

[0005] 2. There are many pores inside the material (higher porosity at the grain boundaries), which not only reduces the density of the material but also may affect its structural integrity and electrochemical performance.

[0006] 3. Excessive processing costs: Traditional physical grinding methods are expensive and inefficient, leading to increased overall production costs.

[0007] 4. Damage to the structure caused by gas production during the synthesis process: During the material synthesis process, gas may be produced due to chemical reactions, which will cause damage to the material structure and affect its performance. For example, irregular and uneven micropores or mesopores may be formed due to fluctuations in local air pressure or gas release during the synthesis process, further reducing the bulk density and compaction density of the material.

[0008] 5. Relying solely on physical grinding during the processing stage: Over-reliance on physical methods to process materials without the assistance of chemical methods may result in substandard material performance.

[0009] 6. Low synthesis efficiency: Existing synthesis methods may have low efficiency due to low solid content, which is not conducive to large-scale production and cost reduction.

[0010] 7. Insufficient electrochemical performance: Due to the above problems, the electrochemical performance of the material may not reach the optimum. For example, the cycle stability and rate performance may not be ideal. In addition, the insufficient kinetic performance is also a key factor restricting its application under high-rate charge and discharge conditions, and it will also cause a rapid decay of the charge and discharge cycle life in low-temperature scenarios.

[0011] 8. Limited industrial application: Due to cost and performance limitations, the industrial application of NFPP materials in sodium-ion batteries faces challenges. The preparation cost and process complexity also become bottlenecks restricting their large-scale production and commercial application.

[0012] These technical problems need to be solved through innovative methods and processes to improve the performance of NFPP materials and reduce production costs, thereby promoting their wide application in the field of sodium-ion batteries. Therefore, it is particularly urgent to develop a new high tap density composite sodium iron phosphate material. Summary of the Invention

[0013] The purpose of the present invention is to provide a preparation method and application of high tap density composite sodium iron phosphate with high tap density, enhanced kinetic performance of the material, improved thermal stability and chemical stability, good electrochemical performance, and low production cost in view of the above existing problems and deficiencies.

[0014] Through an innovative synthesis strategy, the present invention aims to improve the tap density of the material, reduce porosity, improve kinetic performance, and at the same time reduce the synthesis cost, in order to comprehensively improve the performance of sodium-ion batteries and promote the development and application of sodium-ion battery technology.

[0015] The technical solution of the present invention is realized as follows:

[0016] The preparation method of the high tap density composite sodium iron phosphate described in the present invention includes the following steps:

[0017] Step (1), a sodium source, an iron source, and a phosphorus source are weighed according to the stoichiometric ratio of [xNa+(a - x)A]:[yFe+(b - y)B]:P = a:b:(c + 2), where A is a Na-site dopant, B is an Fe-site dopant, A is a metal doping element with a similar ionic radius to Na ions, B is a metal doping element with an ionic radius equal to or smaller than the ionic radius of Fe ions, and 3 ≤ a ≤ 4.3, 2 ≤ b ≤ 3, 1 ≤ c ≤ 2, a - b ≤ 1, 0 < a - x ≤ 0.05, 0 < b - y ≤ 0.05; then the iron source, sodium source, phosphorus source, and a green biodegradable chelating agent are mixed and dispersed in pure water, reacted at a certain temperature for a period of time, then transferred to a sand mill (grinding at a speed of 2800 - 3500 rpm / min), an appropriate amount of dispersant and sucrose are added, and after continuing to grind for a period of time, dopants A and B are added. After grinding, slurry F is obtained.

[0018] Step (2), spray drying the slurry F in a spray drying tower (inlet temperature 220°C, outlet temperature 110°C), spray drying to obtain powder K. The particle size of powder K is controlled at 2 μm. <D10<6um,10um<D50<18um,25um<D99<40um;

[0019] Step (3), the powder K is transferred to a tube furnace, calcined at a temperature between 450-600°C for 10-15 hours under a N2 protective atmosphere with an oxygen content of <50ppm, and finally air flow pulverized to obtain a compound having a high compaction density of the molecular formula (Na x A a-x )(Fe y B b-y )(PO4) c Sodium iron phosphate pyrophosphate positive electrode material powder of P2O7.

[0020] In the present invention, the ratio of the Na-site dopant A and the Fe-site dopant B used as doping elements should be controlled within 0.05. Too high a ratio will result in a significant reduction in performance.

[0021] Furthermore, a:b:(c+2) is 4:3:4 or 3.4:2.4, 3.4, and the latter ratio is preferred.

[0022] In step (1), the amount of chelating agent added is 5%-15% of the total mass of the iron source, sodium source and phosphorus source, and the amount of dispersant added is 1%-3% of the total mass of the iron source, sodium source, phosphorus source and chelating agent. During grinding, the grinding chamber temperature is regulated to be between 30-50°C, and the viscosity of slurry F is between 300-2000mpa*s. The particle size of slurry F is controlled to be D10≤150nm, D50≤300nm, D90≤500nm, Dmax<1um, and the particle size distribution [defined by span=(D90-D10) / D50] is required to be <1.5.

[0023] In the raw materials of the present invention, one or more green and degradable chelating agents are used to prepare the reaction materials into a solution without insoluble matter through chemical corrosion dissolution and chelation, and then cooperate with the physical effect of mechanical sand milling to achieve uniform mixing at the atomic level, and then spray drying and calcination are used to obtain NFPP electrode materials with dense structure, high phase purity and high compaction density. This technology can be named ion chelation preparation technology (Ionic Chelation Preparation Technique).

[0024] In addition, the ratio of PO4 and P2O7 should be considered in the raw material ratio, and the ratio is C:1. 1≤c≤2. This ensures that the reaction process does not cause additional impact on the structure and does not reduce the porosity of the structure, thereby increasing the compaction density of the electrode made of the material. 2-The ratio of P2O7 is because when the material is sintered, if the phosphate group is in excess compared to the designed molecular formula, 2 PO4 2- Lose one O to become P2O7 4- , which will release additional oxygen gas and lead to the appearance of mesopores or micropores.

[0025] The present invention controls the ratio of phosphate (PO4 source) and pyrophosphate (P2O7 source) in the raw materials. When PO4 is greater than 2, the PO4 ratio is too high, which has the following adverse effects: 1. The electronic insulation of the material increases, thereby reducing the conductivity and ion diffusion rate, affecting the charge and discharge performance of the battery. 2. Excessive PO4 3 - May lead to an increase in the bond strength in the crystal structure and improve the structural stability of the material, but at the expense of a certain electrochemical activity. 3. Higher po4 3 - ratio will improve the thermal stability of the material, because po4 3 - helps to form a more stable crystal structure. 4. In some cases, higher po4 3 - ratio may improve the chemical stability of the material, thereby improving the safety of the battery. When PO4 is less than 1, the PO4 ratio is low, and the adverse effects are: 1. Lower PO4 3 - The ratio may reduce the stability of the material; 2. Too little po4 3 - May reduce the bonding strength of the crystal structure, affecting the mechanical stability and cycle stability of the material. 3. Lower po4 3 - ratio may reduce the thermal stability of the material and increase the risk of thermal runaway. 4. Lower po4 3 -ratios may make the materials more vulnerable to chemical attack and increase the risk of side reactions, thus affecting the safety of the battery.

[0026] In addition, ionic strength (I) is a measure of the total amount of ions in a solution and is usually used to describe the concentration level of ions in a solution. Ionic strength affects many physical and chemical processes in a solution, including solubility, reaction rate, and equilibrium. The calculation formula for ionic strength is as follows:

[0027]

[0028] in:

[0029] I is the ionic strength, usually expressed in moles per liter (mol / L).

[0030] ·c i is the concentration of the i-th ion, in moles per liter (mol / L).

[0031] zi is the charge of the ith ion (e.g., for Na +, zi = +1; for Cl - , zi = -1; for Ca 2+ , zi=+2, etc.)

[0032] In the process of preparing composite sodium iron phosphate by ion chelation preparation technology, the ion concentration will significantly affect the progress of the chelation reaction, which is specifically manifested in solubility, coordination equilibrium, chelation constant, ligand dissociation, charge distribution, reaction kinetics, etc. Therefore, the ionic strength needs to be controlled within a certain range. The present invention controls it within I=0.03-0.1 mol / L to obtain the best reaction effect.

[0033] Here we calculate the equilibrium constant Kf (i.e. equilibrium condition) of the chelate (chelate formed by chelating agent and iron ion):

[0034]

[0035] Wherein, [Fe]0 and [L]0 are the initial concentrations of iron ions and chelating agent at the beginning of the reaction, respectively, and [Fe] and [L] are the concentrations of iron ions and chelating agent at equilibrium in the solution, respectively.

[0036] Combined with the Debye-Hückel theory,

[0037] where A is the Debye-Hückel constant, γ i is the activity coefficient (which can be considered as 1 at low concentrations), and zi is the charge number of the ion; according to this formula, the equilibrium relationship of the final chelation reaction is

[0038]

[0039] According to this formula and combined with actual conditions, when the concentration of chelating agent is constant, it is found that lg(K f )>-2, indicating that the chelation reaction is very fast, and the chelating agent has a good chelating effect on the iron source, -6 <lg(K f )<-2, indicating that the chelation reaction is slow and the chelating agent has a general effect. f )<-6, indicating that the reaction hardly occurs, indicating that the chelating agent is ineffective.

[0040] In addition, the concentration of ion chelators needs to be controlled within a certain range, because too low or too high a concentration may have an adverse effect on the effect of the chelation reaction.

[0041] Inadequate chelating agent concentrations may:

[0042] Insufficient chelation: Too low a chelating agent concentration may result in insufficient chelating agent for the metal ions to react with, thus failing to fully chelate and affecting the chelation efficiency.

[0043] Slow reaction rate: Lower chelating agent concentrations may slow the rate of the chelation reaction and increase the time required to reach equilibrium.

[0044] Reduced selectivity: In the presence of multiple metal ions, a chelator concentration that is too low may not be able to effectively distinguish and selectively chelate specific ions.

[0045] When the concentration is too high, it may:

[0046] Increased side reactions: Too high a chelating agent concentration may cause undesirable side reactions such as over-chelation or reaction with other components in the solution.

[0047] Precipitate Formation: Some chelating agents may form a precipitate at high concentrations, which can reduce their effective concentration in solution and may clog equipment.

[0048] Increased costs: Using excessive amounts of chelating agents will increase the cost of raw materials, which is not cost-effective from an economic perspective.

[0049] Toxicity issues: Some chelating agents may be toxic to the environment or operators at high concentrations.

[0050] In the present technical solution, the dosage of the chelating agent is limited by the ratio of the ion concentration of the chelating agent to the total ion concentration in the solution. The optimal range of this parameter in the present invention is 0.005-0.03.

[0051] The sodium source in the present invention is from compounds such as carbonates, sulfates, oxides, chlorides, borides, hydroxides, etc., including but not limited to sodium hydroxide (NaOH), sodium carbonate (Na2CO3), sodium chloride (NaCl), sodium pyrophosphate (Na4P2O7), disodium dihydrogen pyrophosphate (Na2H2P2O7), sodium nitrate (NaNO3), sodium bicarbonate (NaHCO3), sodium oxide (Na2O), sodium borohydride (NaBH4), sodium borate (Na2B4O7). The iron source is from compounds such as carbonates, sulfates, oxides, chlorides, phosphates, borides, hydroxides, etc., including but not limited to ferrous sulfate (FeSO4), ferrous sulfate (Fe2(SO4)3), ferrous chloride (FeCl2), ferric chloride (FeCl3), ferrous nitrite (Fe(NO2)2), ferrous nitrite (Fe(NO2)3), ferrous nitrate (Fe(NO3)2), ferric nitrate (Fe(NO3)3), ferric phosphate (FePO4), and ferric oxide (Fe2O3). The phosphorus source is derived from compounds such as phosphates, chlorides, and oxides, including but not limited to sodium dihydrogen phosphate (NaH2PO4), sodium trihydrogen phosphate (Na3PO4), disodium hydrogen phosphate (Na2HPO4), trisodium hydrogen phosphate (Na2H2PO4), monosodium phosphate (NaH2PO3), disodium phosphate (Na2HPO3), trisodium phosphate (Na3PO3), phosphorus chloride (PCl3), phosphorus oxide (P2O5), sodium phosphite (NaH2PO2), and ammonium dihydrogen phosphate (NH4H2PO4); the chelating agent is derived from ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), sodium hypophosphite, citric acid, oxalic acid, ascorbic acid, tartaric acid, ethylenediaminedi-o-phenylacetic acid (EDDHA), hydroxyethylethylenediaminetriacetic acid (HEDTA), propylenediaminetetraacetic acid (PDTA), nitrilotriacetic acid (NTA), salicylic acid, phenolsulfonic acid (Phenolsulfonic Acid), tetrasodium iminodisuccinate (IDS-Na4), tetrasodium glutamate diacetate (GLDA-Na4), tetrasodium aspartate diacetate (ASDA-Na4), trisodium methylglycine diacetate (MGDA-Na3);

[0052] The dispersant is one or more of polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), methyl hydroxyethyl cellulose (MHEC), sodium tripolyphosphate (STPP), and sodium dodecyl sulfate (SDS).

[0053] The composite sodium iron phosphate of the present invention can be widely used in positive electrode materials of sodium ion batteries.

[0054] Compared with the prior art, the present application has the following beneficial effects:

[0055] 1. Improved compaction density: By using raw materials containing chelating agents, it is ensured that the iron source exists completely in the material in an ionic state, which helps to form a high-purity NFPP phase, improve the intrinsic density of the material (intrinsic density is also called true density, reaching 3.4-3.8), thereby improving the compaction density of the material (compaction density reaches 2.2-2.5). In addition, because the ion concentration will significantly affect the progress of the chelation reaction during the preparation of the composite sodium iron phosphate using the ion chelation preparation technology, the present invention controls the ion strength within the range of 0.03-0.1 mol / L to obtain the best reaction effect.

[0056] 2. Reduced porosity: By controlling the ratio of pyrophosphate to phosphate in the raw materials, the release of gases (such as oxygen, carbon dioxide, etc.) during the material formation process is avoided, and the impact on the crystal structure of the material is reduced, thereby reducing the formation of pores and reducing the porosity.

[0057] 3. Improved crystal structure: By precisely controlling the ratio of pyrophosphate to phosphate, the destruction of the crystal structure by gas release is avoided, making the secondary grains complete and orderly, and improving the overall density of the material.

[0058] 4. Enhanced kinetic properties: Due to the presence of the iron source in an ionic state and the optimized crystal structure, it can be expected that the ion diffusion properties of the material will be improved, thereby enhancing the kinetic properties of the material.

[0059] 5. Reduced synthesis cost: The optimization of raw material processing and synthesis process mentioned in the present invention can simplify the production process, reduce energy consumption and the use of raw materials, and increase the solid content in the feed solution, thereby reducing the synthesis cost.

[0060] 6. Improved material stability: By reducing gas release, possible structural damage of the material during the synthesis process is avoided, and the thermal and chemical stability of the material is improved.

[0061] 7. Optimized the electrochemical properties of the material: Through the above improvements, it is expected that the electrochemical properties of the material, such as cycle stability, rate performance and high temperature performance, will be significantly improved.

[0062] 8. Simplified process flow: If the material preparation can be achieved through chemical corrosion dissolution and physical process assistance, the traditional sand grinding and spray drying processes can be simplified and the dependence on equipment can be reduced.

[0063] 9. Improved material safety: By reducing porosity and optimizing the crystal structure, the mechanical and thermal stability of the material during battery charging and discharging may be enhanced, thereby improving battery safety.

[0064] These improvement points directly address the deficiencies of existing sodium iron phosphate composite materials in terms of tap density, porosity, and kinetic performance, significantly enhancing the material's performance and meeting the requirements of sodium-ion batteries for high energy density and high power density applications.

[0065] The present invention will be further described below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 SEM diagram of an embodiment of the present invention.

[0067] Figure 2 XRD diagram of an embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0068] The present invention relates to a method for preparing a high tap density sodium iron phosphate composite, comprising the following steps:

[0069] Step (1): Weigh the sodium source, iron source, and phosphorus source according to the stoichiometric ratio of [xNa+(a-x)A]:[yFe+(b-y)B]:P = a:b:(c+2), where A is a Na-site dopant, B is an Fe-site dopant, A is a metal doping element with a similar ionic radius to Na ions, B is a metal doping element with an ionic radius equal to or smaller than that of Fe ions, and 3 ≤ a ≤ 4.3, 2 ≤ b ≤ 3, 1 ≤ c ≤ 2, a-b ≤ 1, 0 < a-x ≤ 0.05, 0 < b-y ≤ 0.05; then mix and disperse the iron source, sodium source, phosphorus source, and green biodegradable chelating agent into pure water, react at a certain temperature for a period of time, then transfer to a sand mill (grind at a speed of 2800 - 3500 rpm / min), add an appropriate amount of dispersant and sucrose, continue grinding, and then add A and B. After grinding, slurry F is obtained.

[0070] Step (2): Spray-dry slurry F using a spray drying tower, with an inlet temperature of 220°C and an outlet temperature of 110°C, to obtain powder K. The particle size of powder K is controlled such that 2um < D10 < 6um, 10um < D50 < 18um, 25um < D99 < 40um;

[0071] Step (3): Transfer powder K to a tubular furnace, calcine it for 10 - 15 hours at a temperature between 450 - 600°C under a N2 protective atmosphere with an oxygen content < 50 ppm, and finally obtain a sodium iron phosphate pyrophosphate positive electrode material powder with a high tap density and a molecular formula of (Na x A a-x )(Fe y B b-y )(PO4) c P2O7 by air flow pulverization.

[0072] In step (1) of the present invention, sucrose is used as a carbon source and a reducing agent (reducing trivalent Fe to divalent Fe). Its role as a carbon source is similar to the carbon coating of lithium iron phosphate. The controlled amount of sucrose is 0%-2% of the total mass.

[0073] Preferably, a:b:(c+2) is 4:3:4 or 3.4:2.4, 3.4, and the latter ratio is preferred.

[0074] During grinding, the grinding chamber temperature is regulated to be between 30 and 50° C., and the viscosity of the slurry F is between 300 and 2000 mPa*s. The amount of the chelating agent added is 5% to 15% of the total mass of the iron source, the sodium source and the phosphorus source, and the amount of the dispersant added is 1% to 3% of the total mass of the iron source, the sodium source, the phosphorus source and the chelating agent.

[0075] During grinding in step (1), the grinding chamber temperature is regulated between 30-50°C, the particle size of the slurry F is controlled, and the viscosity is controlled between 300-2000 mpa*s. The particle size of the slurry F is controlled within the range of D10≤150nm, D50≤300nm, D90≤500nm, Dmax<1um, and the particle size distribution [defined as span=(D90-D10) / D50] is <1.5.

[0076] In step (1), the ionic strength of the chelating agent is controlled within the range of I=0.03-0.1 mol / L.

[0077] The ratio of the ion concentration of the chelating agent to the total ion concentration in the solution is 0.005-0.03.

[0078] The present invention is further described in detail below in conjunction with specific embodiments:

[0079] Embodiment 1:

[0080] Step (1): weigh sodium pyrophosphate: lithium hydroxide: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio of 1.0: 0.02: 1.485: 0.015: 2, a total of 2000 g, first disperse ferric oxide, sodium pyrophosphate and ammonium dihydrogen phosphate in pure water, then add 145 g of ethylenediaminetetraacetic acid, 25 g of citric acid and 25 g of ascorbic acid as chelating agents, react in a reactor at 60° C. for 12 h, then transfer to a sand mill and grind at a speed of 3000 r / min, add 20 g of sodium dodecyl sulfate as a dispersant and 30 g of sucrose after grinding for 1 h, and then add the remaining materials lithium hydroxide and neodymium oxide after grinding for 3 h. During grinding, the grinding chamber temperature is adjusted to 40° C. After grinding, the particle size of the slurry F is controlled, and the particle size distribution is D10: 100-150 nm; D50: 200-300 nm; D90: 300-500 nm. At the same time, the viscosity of slurry F is <1000mpa*s;

[0081] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10: 5-6 um, D50: 10-14 um, and D99: 25-30 um;

[0082] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 0.02 )(Fe 2.97 Nd 0.03 Sodium iron phosphate pyrophosphate powder of )(PO4)2P2O7.

[0083] Embodiment 2:

[0084] Step (1): weigh sodium pyrophosphate: lithium hydroxide: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio = 0.85: 0.02: 1.2: 0.015: 1.4, a total of 2000 g, first disperse ferric oxide, sodium pyrophosphate, and ammonium dihydrogen phosphate in pure water, then add 145 g of ethylenediaminetetraacetic acid, 25 g of citric acid, and 25 g of ascorbic acid as a chelating agent, react in a reactor at 60° C. for 12 h, and then transfer to a sand mill. The mill was ground at a speed of 3000r / min. After grinding for 1h, 20g of sodium dodecyl sulfate as a dispersant and 30g of sucrose were added. After grinding for another 3h, the remaining materials were added. The grinding chamber temperature was regulated at 40°C during grinding. After grinding, the particle size of the slurry F was controlled. The particle size distribution was D10: 100-150nm; D50: 200-300nm; D90: 300-500nm. At the same time, the viscosity of the slurry was <1000mpa*s.

[0085] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10: 5-6 um, D50 ≤ 14 um (10-14), and D99: 25-30 um;

[0086] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 3.4 Li 0.02 )(Fe 2.4 Nd 0.03 )(PO4) 1.4 Sodium iron phosphate pyrophosphate powder of P2O7.

[0087] This embodiment is a preferred embodiment. The SEM diagram of this embodiment is shown in Figure 1 , xrd diagram see Figure 2 .from Figure 1It can be seen that the material has few micropores and low porosity; Figure 2 This indicates that the material is prepared according to the method, has no impurities and is of high purity.

[0088] Embodiment 3:

[0089] Step (1): weigh sodium pyrophosphate: lithium hydroxide: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio of 0.85:0.02:1.2:0.015:1.4, a total of 2000 g, first disperse ferric oxide, sodium pyrophosphate, and ammonium dihydrogen phosphate in pure water, then add 145 g of hydroxyethylethylenediaminetriacetic acid, 25 g of anhydrous oxalic acid, and 25 g of ascorbic acid as a chelating agent, react in a reactor at 60° C. for 12 h, and then transfer to The sand mill was ground at a speed of 3000 r / min. After grinding for 1 hour, 20 g of sodium dodecyl sulfate as a dispersant and 30 g of sucrose were added. After grinding for another 3 hours, the remaining materials were added. The grinding chamber temperature was adjusted to 40°C during grinding. After grinding, the particle size of the slurry F was controlled. The particle size distribution was D10: 100-150 nm; D50: 200-300 nm; D90: 300-500 nm. At the same time, the viscosity of the slurry was <1000 mpa*s.

[0090] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0091] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 3.4 Li 0.02 )(Fe 2.4 Nd 0.03 )(PO4) 1.4 Sodium iron phosphate pyrophosphate powder of P2O7.

[0092] Based on Example 2, the chelating agent was changed.

[0093] Example 4

[0094] Step (1): weigh sodium pyrophosphate: potassium hydroxide: ferrous oxalate: lanthanum oxide: phosphoric acid according to the stoichiometric ratio = 0.85: 0.02: 2.4: 0.015: 1.4, a total of 2000g, first disperse ferrous oxalate, sodium pyrophosphate and phosphoric acid in pure water, then add 145g of ethylenediaminetetraacetic acid, 25g of citric acid and 25g of ascorbic acid as chelating agents, react in a reactor at 60°C for 12h, then transfer to a sand mill and grind at a speed of 3000r / min, add 20g of sodium dodecyl sulfate as a dispersant and 30g of sucrose after grinding for 1h, and then add the remaining materials after grinding for 3h, adjust the grinding chamber temperature at 30-50°C during grinding, and control the particle size of slurry F after grinding, and the particle size distribution is D10: 100-150nm; D50: 200-300nm; D90: 300-500nm, and the viscosity of the slurry is <1000mpa*s;

[0095] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0096] Step (3): The powder K is transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally air flow crushed to obtain sodium iron pyrophosphate powder. The molecular formula is (Na 3.4 K 0.02 )(Fe 2.4 La 0.03 )(PO4) 1.4 P2O7. Compared with Example 2, the doping element is changed.

[0097] Comparative Example 1

[0098] Step (1): weigh sodium pyrophosphate: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio of 0.85:1.2:0.015:1.4, a total of 2000 g, first disperse ferric oxide, sodium pyrophosphate, and ammonium dihydrogen phosphate in pure water, then add 145 g of ethylenediaminetetraacetic acid, 25 g of citric acid, and 25 g of ascorbic acid as a chelating agent, react in a reactor at 60° C. for 12 h, then transfer to a sand mill and grind at a speed of 3000 r / min, grind for 1 h, then add 20g sodium dodecyl sulfate as a dispersant and 30g sucrose are added, and the remaining materials are added after grinding for 3 hours. The temperature of the grinding chamber is adjusted to be lower than 50°C during grinding. After grinding, the particle size of the slurry F is controlled, and the particle size distribution is D10: 100-150nm; D50: 200-300nm; D90: 300-500nm, and the particle size distribution is D10: 0.1-0.15um; D90: 0.3-0.5nm, and the viscosity of the slurry is <1000mpa*s;

[0099] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0100] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 3.4 (Fe 2.4 Nd 0.03 )(PO4) 1.4 Sodium iron phosphate pyrophosphate powder of P2O7.

[0101] Compared with the preferred embodiment 2, this embodiment does not have Na doping, and also uses the chelating agent preparation method.

[0102] Comparative Example 2

[0103] Step (1): weigh sodium pyrophosphate: lithium hydroxide: ferric oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio = 0.85: 0.02: 1.2: 1.4, a total of 2000g, first disperse ferric oxide, sodium pyrophosphate, and ammonium dihydrogen phosphate in pure water, then add 145g of ethylenediaminetetraacetic acid, 25g of citric acid, and 25g of ascorbic acid as a chelating agent, react in a reactor at 60°C for 12h, then transfer to a sand mill and grind at a speed of 3000r / min, add 20g of sodium dodecyl sulfate as a dispersant and 30g of sucrose after grinding for 1h, and then add the remaining materials after grinding for 3h, adjust the grinding chamber temperature to be lower than 50°C during grinding, and control the particle size of slurry F after grinding, and the particle size distribution is D10: 100-150nm; D50: 200-300nm; D90: 300-500nm, and the viscosity of the slurry is <1000mpa*s;

[0104] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0105] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 3.4 Li 0.02 )Fe 2.4 (PO4) 1.4 Sodium iron phosphate pyrophosphate powder of P2O7.

[0106] Compared with the preferred embodiment 2, this embodiment does not have Fe doping and also uses the chelating agent preparation method.

[0107] Comparative Example 3:

[0108] Step (1): weigh sodium pyrophosphate: lithium hydroxide: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio of 1.0: 0.02: 1.485: 0.015: 2.1, a total of 2000 g, first disperse ferric oxide, sodium pyrophosphate and ammonium dihydrogen phosphate in pure water, then add 145 g of ethylenediaminetetraacetic acid, 25 g of citric acid and 25 g of ascorbic acid as chelating agents, react in a reactor at 60° C. for 12 h, then transfer to a sand mill and grind at a speed of 3000 r / min, add 20 g of sodium dodecyl sulfate as a dispersant and 30 g of sucrose after grinding for 1 h, and then add the remaining materials lithium hydroxide and neodymium oxide after grinding for 3 h. During grinding, the grinding chamber temperature is adjusted to be lower than 50° C. After grinding, the particle size of the slurry F is controlled, and the particle size distribution is D10: 100-150 nm; D50: 200-300 nm; D90: 300-500 nm. At the same time, the viscosity of slurry F is <1000mpa*s;

[0109] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0110] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 0.02 )(Fe 2.97 Nd 0.03 )(PO4) 2.1 Sodium iron phosphate pyrophosphate powder of P2O7.

[0111] Comparative Example 1, the embodiment here is designed as PO4:P2O7=2.1:1.

[0112] Comparative Example 4:

[0113] Step (1): weighing sodium pyrophosphate: lithium hydroxide: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio of 1.0: 0.02: 1.485: 0.015: 2, a total of 2000 g, adding the materials into pure water in turn, stirring for 3 hours to disperse evenly, and then transferring them to a sand mill and grinding at a speed of 3000 r / min. After grinding for 1 hour, 20 g of sodium dodecyl sulfate as a dispersant and 30 g of sucrose are added, and the remaining materials are added after grinding for another 3 hours. During grinding, the temperature of the grinding chamber is adjusted to be lower than 50° C. After grinding, the particle size of the slurry F is controlled, and the particle size distribution is D10: 100-150 nm; D50: 200-300 nm; D90: 300-500 nm, and the viscosity of the slurry is <1000 mpa*s;

[0114] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0115] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 0.02 )(Fe 2.97 Nd 0.03 Sodium iron phosphate pyrophosphate powder of )(PO4)2P2O7.

[0116] Comparative Example 1, without using a chelating agent method.

[0117] Comparative Example 5:

[0118] Step (1): weigh sodium pyrophosphate: potassium hydroxide: ferrous oxalate: lanthanum oxide: phosphoric acid according to the stoichiometric ratio = 0.85: 0.02: 2.4: 0.015: 1.4, a total of 2000g, first disperse ferrous oxalate, sodium pyrophosphate and phosphoric acid into pure water, then add, react in a reactor at 60°C for 12h, then transfer to a sand mill and grind at a speed of 3000r / min, add 20g of sodium dodecyl sulfate as a dispersant and 30g of sucrose after grinding for 1h, and then add the remaining materials after grinding for 3h, adjust the grinding chamber temperature to below 50°C during grinding, and control the particle size of slurry F after grinding, and the particle size distribution is D10: 100-150nm; D50: 200-300nm; D90: 300-500nm, and the viscosity of the slurry is <1000mpa*s;

[0119] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0120] Step (3): The powder K is transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally air flow crushed to obtain sodium iron pyrophosphate powder. The molecular formula is (Na 3.4 K 0.02 )(Fe 2.4 La 0.03 )(PO4) 1.4 P2O7.

[0121] Comparative Example 4, without using a chelating agent.

[0122] Comparative Example 6:

[0123] Step (1): weigh sodium pyrophosphate: lithium hydroxide: ferric oxide: neodymium oxide: ammonium dihydrogen phosphate according to the stoichiometric ratio = 1.0: 0.02: 1.485: 0.015: 2.1, a total of 2000g, first disperse ferric oxide, sodium pyrophosphate, and ammonium dihydrogen phosphate in pure water, react in a reactor at 60°C for 12 hours, then transfer to a sand mill and grind at a speed of 3000r / min, add 20g of sodium dodecyl sulfate as a dispersant and 30g of sucrose after grinding for 1 hour, and then add the remaining materials lithium hydroxide and neodymium oxide after grinding for 3 hours. During grinding, the grinding chamber temperature is adjusted to be lower than 50°C. After grinding, the particle size of slurry F is controlled, and the particle size distribution is D10: 100-150nm; D50: 200-300nm; D90: 300-500nm. At the same time, the viscosity of slurry F is <1000mpa*s;

[0124] Step (2): spray drying the slurry F in a spray drying tower, with an inlet temperature of 220° C. and an outlet temperature of 110° C., spray drying to obtain powder K, and controlling the particle size of powder K to be D10 ≥ 5 μm, D50 ≤ 14 μm, and D99 ≤ 30 μm;

[0125] Step (3): The powder K was transferred to a tube furnace, calcined at 580°C for 15 hours under a N2 protective atmosphere, and finally pulverized by air flow to obtain a 0.02 )(Fe 2.97 Nd 0.03 )(PO4) 2.1 P2O7 sodium ferric pyrophosphate powder.

[0126] Compared with Comparative Example 3, no chelating agent was used.

[0127] Battery testing part: The sodium iron phosphate pyrophosphate material prepared above is used to prepare a sodium ion battery electrode, including the following steps:

[0128] (1) Take polyvinylidene fluoride (PVDF) with a molecular weight of 800,000 to 1,000,000, bake it under vacuum at 80°C for 10 hours, then slowly add it to 2850g of N-methylpyrrolidone, stir it under vacuum at 700rpm for 30min, and let it stand to obtain a 5% (same as above) adhesive slurry; the amount of PVDF added after baking is 150g.

[0129] (2) 681.5 g of CNT and 25 g of conductive carbon black (Super P) pre-baked at 120 °C under vacuum for 12 h were added to the adhesive slurry. After vacuum stirring at 700 rpm for 2 h, 5000 g of sodium-based layered oxide material pre-baked at 120 °C under vacuum for 12 h was added. Vacuum stirring was continued at 700 rpm for 2 h, and then an appropriate amount of NMP was added to adjust the viscosity to 5000 mPa·s.

[0130] (3) The main material prepared in step (2) is coated on an aluminum foil with a thickness of 12 μm and dried to remove the solvent. After rolling and slitting, a composite positive electrode sheet is obtained.

[0131] Furthermore, the preparation of a soft-pack battery using the composite positive electrode sheet obtained above comprises the following steps:

[0132] (1) hard carbon, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) are dissolved in deionized water in a mass ratio of 100:15:10, stirred evenly to form a slurry, coated on a copper current collector, and dried, and then rolled and cut to obtain a negative electrode sheet;

[0133] (2) The positive electrode sheet, the negative electrode sheet and the separator are made into a core by adopting a lamination process, and a 15Ah aluminum-plastic film soft-pack battery is obtained by packaging, liquid injection, formation, evacuation and sealing.

[0134] The physical and chemical properties of the sodium iron pyrophosphate powder obtained in the above examples were tested, and the test results are as follows:

[0135] Table 1 Physical and chemical properties

[0136]

[0137]

[0138] From the results, Example 2 has the best overall performance, achieving the lowest resistivity and the highest true density, indicating that the chelating agent formula of Example 2 has the best effect. Comparative Examples 1 and 2 have significantly improved resistivity relative to Example 2 because there is no Na-doping and Fe-doping. The true density is also reduced. Comparative Examples 4 and 5 have significantly improved resistivity relative to Examples 1 and 4 because no chelating agent is used, and the true density and tap density are also reduced. Comparative Example 6 has a lower specific capacity relative to Comparative Example 3 because no chelating agent is used, and the true density and tap density are low, and the resistivity is also relatively large.

[0139] Table 2 Synthesis process parameters

[0140]

[0141] From the data in Table 2, it can be found that the type and proportion of the chelating agent used in Example 2 are relatively suitable, and the maximum equilibrium constant is achieved, indicating that the reaction efficiency of the chelating agent in Example 2 is the best.

[0142] Table 3 Electrochemical indicators of button batteries

[0143]

[0144] It can be seen from the table that Example 2 achieves the best overall half-cell test level, with the highest specific capacity, first efficiency and compaction density. It can also be seen from the data in the above table that compared with Comparative Example 3, Example 1 will produce impurities because the ratio of PO4 to P2O7 in Comparative Example 3 exceeds the range of 2:1, and the intuitive impact is that the specific capacity is greatly reduced.

[0145] Table 4 Electrochemical indicators of 15Ah soft pack battery

[0146]

[0147] It can be seen from Table 4 that the soft-pack battery prepared using the material of Example 2 with the best performance has the best performance, which is reflected in the fact that the compaction density of the electrode reaches 2.63g / cc, the first-cycle coulomb efficiency is 88.5%, the cycle process is very stable, and the final energy density of the soft-pack battery reaches 128Wh / kg, which is very beneficial to the application of this material in energy storage scenarios and two-wheel vehicle scenarios.

[0148] Although the present invention is described with reference to specific embodiments, such description is not intended to limit the present invention. With reference to the description of the present invention, other changes of the disclosed embodiments are predictable to those skilled in the art, and such changes should fall within the scope defined by the claims.

Claims

1. A method for preparing a high compacted density composite sodium iron phosphate, characterized in that It includes the following steps: Step (1): Weigh the sodium source, iron source, and phosphorus source according to the stoichiometric ratio of [xNa+(a-x)A]:[yFe+(b-y)B]:P = a:b:(c+2), where A is a Na-site dopant, B is an Fe-site dopant, A is a metal doping element with a similar ionic radius to Na ions, B is a metal doping element with an equal or smaller ionic radius than Fe ions, and 3 ≤ a ≤ 4.3, 2 ≤ b ≤ 3, 1 ≤ c ≤ 2, a - b ≤ 1, 0 < a - x ≤ 0.05, 0 < b - y ≤ 0.

05. Then, mix and disperse the iron source, sodium source, phosphorus source, and a green biodegradable chelating agent into pure water, react at a certain temperature for a period of time, then transfer to a sand mill for grinding. Next, add an appropriate amount of dispersant and sucrose, continue grinding for a period of time, and then add dopants A and B. After grinding, obtain slurry F. Step (2): Spray-dry slurry F using a spray drying tower to obtain powder K. Step (3), the powder K is transferred to a tube furnace, calcined at a temperature between 450-600°C for 10-15 hours under a N2 protective atmosphere with an oxygen content of <50ppm, and finally air flow crushed to obtain a high compaction density of the molecular formula (Na x A a-x )(Fe y B b-y )(PO4) c Sodium iron phosphate pyrophosphate positive electrode material powder of P2O7.

2. The method for preparing high compacted density composite sodium iron phosphate according to claim 1, characterized in that: In step (1), the addition amount of the chelating agent is 5% - 15% of the total mass of the iron source, sodium source, and phosphorus source, and the addition amount of the dispersant is 1% - 3% of the total mass of the iron source, sodium source, phosphorus source, and chelating agent.

3. The method for preparing the high compacted density composite sodium iron phosphate according to claim 1, characterized in that: During grinding in step (1), control the temperature of the grinding chamber to be between 30 - 50°C, control the particle size of slurry F, and at the same time control the viscosity to be between 300 - 2000 mPa·s.

4. The method for preparing the high compacted density composite sodium iron phosphate according to claim 1, characterized in that: In step (1), the ionic strength of the chelating agent is controlled within the range of I = 0.03 - 0.1 mol / L.

5. The method for preparing the high compacted density composite sodium iron phosphate according to claim 1, characterized in that: The ratio of the ionic concentration of the chelating agent to the total ionic concentration in the solution is 0.005 - 0.

03.

6. The preparation method of the high tap density sodium iron phosphate composite according to claim 1, characterized in that: The particle size of slurry F is controlled such that D10 ≤ 150 nm, D50 ≤ 300 nm, D90 ≤ 500 nm, Dmax < 1 μm, and the particle size distribution is < 1.5; the particle size of powder K is controlled such that 2 μm < D10 < 6 μm, 10 μm < D50 < 18 μm, 25 μm < D99 < 40 μm.

7. The method for preparing the high compacted density composite sodium iron phosphate according to claim 1, characterized in that: The sodium source comes from carbonates, sulfates, oxides, chlorides, borides, hydroxides, including but not limited to sodium hydroxide, sodium carbonate, sodium chloride, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium nitrate, sodium bicarbonate, sodium oxide, sodium borohydride, sodium borate; The iron source comes from carbonates, sulfates, oxides, chlorides, phosphates, borides, hydroxides, including but not limited to ferrous sulfate, ferric sulfate, ferrous chloride, ferric chloride, ferrous nitrite, ferric nitrite, ferrous nitrate, ferric nitrate, iron phosphate, iron oxide.

8. The method for preparing the high compacted density composite sodium iron phosphate according to claim 1, characterized in that: The phosphorus source comes from phosphates, chlorides, oxides, including but not limited to sodium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, sodium hydrogen phosphate, sodium phosphate monobasic, disodium phosphate, trisodium phosphate, phosphorus chloride, phosphorus oxide, sodium phosphite, ammonium dihydrogen phosphate.

9. The method for preparing high compacted density composite sodium iron phosphate according to claim 1, characterized in that: The chelating agent is one or more of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, sodium hypophosphite, citric acid, oxalic acid, ascorbic acid, tartaric acid, ethylenediaminedi-o-phenylacetic acid, hydroxyethylethylenediaminetriacetic acid, propylenediaminetetraacetic acid, nitrilotriacetic acid, salicylic acid, phenolsulfonic acid, tetrasodium iminodisuccinate, tetrasodium glutamate diacetate, tetrasodium aspartate diacetate, and trisodium methylglycine diacetate; The dispersant is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, sodium carboxymethyl cellulose, methyl hydroxyethyl cellulose, sodium tripolyphosphate and sodium dodecyl sulfate.

10. An application of high compacted density composite sodium iron phosphate according to any one of claims 1 to 9, characterized in that: Used in positive electrode materials of sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method and application of high-stability ferric sodium pyrophosphate material

    CN117945378A

  • Preparation method and application of high-energy-density ferric sodium pyrophosphate material

    CN118183670A

  • Preparation method of ferric sodium pyrophosphate composite material as well as obtained material and application thereof

    CN118263424A

  • Positive electrode active material for sodium ion battery and method for producing the same

    JP6101771B1

Cited By

  • Composite sodium ferric phosphate positive electrode material and preparation method thereof

    CN120854463A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN120914251A

  • High-compaction sodium ion battery composite positive electrode, battery cell, single battery and electric equipment

    CN121011634A

  • High-solid-degree composite sodium ferric phosphate positive electrode material, preparation method thereof and battery

    CN121063508A

  • Preparation method of ferric sodium pyrophosphate positive electrode material

    CN121269666A